2017
DOI: 10.1021/acs.joc.7b01188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substituents on the Bond Strength of Air-Stable Dicyanomethyl Radical Thermochromes

Abstract: A series of substituted aryl dicyanomethyl radicals were synthesized, and the bonding thermodynamic parameters for self-dimerization were determined from van't Hoff plots obtained from variable-temperature electron paramagnetic resonance and ultraviolet−visible spectroscopy. At low temperatures, the radicals dimerize, but the colored, air-stable free radicals return upon heating. Heating and cooling cycles (5−95 °C) can be repeated without radical degradation and with striking thermochromic behavior. We find a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 13 publications
2
69
0
Order By: Relevance
“…Dynamic covalent chemistry (DCC) has been attracting increasing interest in the field of molecular self‐assembly . In particular, the reversible formation of covalent bonds based on dimerization–dissociation reactions of organic radicals is the simplest process of dynamic covalent chemistry and does not involve any catalysts or byproducts. Recently, we demonstrated that para ‐amino‐substituted α,α‐dicyanobenzyl radicals are useful motifs for DCC owing to the dynamic equilibrium between the radical form and the dimer formed via a reversible C−C bond (σ‐dimer) .…”
Section: Figurementioning
confidence: 99%
“…Dynamic covalent chemistry (DCC) has been attracting increasing interest in the field of molecular self‐assembly . In particular, the reversible formation of covalent bonds based on dimerization–dissociation reactions of organic radicals is the simplest process of dynamic covalent chemistry and does not involve any catalysts or byproducts. Recently, we demonstrated that para ‐amino‐substituted α,α‐dicyanobenzyl radicals are useful motifs for DCC owing to the dynamic equilibrium between the radical form and the dimer formed via a reversible C−C bond (σ‐dimer) .…”
Section: Figurementioning
confidence: 99%
“…Para electron-donating substitution was found to be crucial for stabilizing aryldicyanomethyl radicals and weakening C(sp 3 )ÀC(sp 3 )bonds formed between them. [6,9] Thus the TPAc ore is used here to facilitate reversible association and dissociation of radicals.Alow dissociation enthalpy of about 55 kJ mol À1 is expected for the corresponding C(sp 3 ) À C(sp 3 )b onds,a sd etermined from ad imer model compound, [6] enabling reversible conversion of the C(sp 3 )ÀC(sp 3 )b ond to radicals at room temperature.…”
mentioning
confidence: 93%
“…[1] In particular,t he reversible formation of covalent bonds based on dimerization-dissociationreactions of organic radicals [2][3][4][5][6][7][8][9][10] is the simplest process of dynamic covalent chemistry and does not involve any catalysts or byproducts.R ecently,w e demonstrated that para-amino-substituted a,a-dicyanobenzyl radicals [2] are useful motifs for DCC owing to the dynamic equilibrium between the radical form and the dimer formed via ar eversible C À Cb ond (s-dimer). [1] In particular,t he reversible formation of covalent bonds based on dimerization-dissociationreactions of organic radicals [2][3][4][5][6][7][8][9][10] is the simplest process of dynamic covalent chemistry and does not involve any catalysts or byproducts.R ecently,w e demonstrated that para-amino-substituted a,a-dicyanobenzyl radicals [2] are useful motifs for DCC owing to the dynamic equilibrium between the radical form and the dimer formed via ar eversible C À Cb ond (s-dimer).…”
mentioning
confidence: 99%